Community-Based Risk Management Arrangements : A Review - Bhattamishra, Ruchira; Barrett, Christopher B. (2012)
Risk and its consequences pose a formidable threat to poverty reduction efforts. This article reviews a plethora of community-based risk management arrangements across the developing world. These types of arrangements are garnering greater interest in light of the growing recognition of the relative prominence of household- or individual-specific idiosyncratic risk as well as the increasing shift towards community-based development funding. The article discusses potential advantages (such as targeting, cost and informational) and disadvantages (such as exclusion and inability to manage correlated risk) of these arrangements, and their implications for the design of community-based social protection programs and policies.